How to handle authorship disputes: a guide for new researchers - Albert, Tim; Wager, Elizabeth (Морфологія / Morphologia / Morfologìâ, 2011)
One of the main objectives of the COPE Education Committee is to reduce the incidence of unethical behavior. This implies a pretty bold step to identify what to call unethical, and then - to make suggestions on how to avoid this in the future.